Низька геномна мінливість в культурі in vitro лінії кукурудзи Black Mexican Sweet Corn C456 - Майданюк, Д.М.; Андрєєв, І.О.; Спірідонова, К.В.; Кунах, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
An analysis of callus tissues of maize Black Mexican Sweet Corn C456 line was performed through RAPD-PCR. 275 amplicons were scored, and only 2 of them were polymorphic. The polymorphic fragments revealed a variability among the plants as well as between the plants and their calluses, that may allow one to assume the existence of “hot spots” with higher variability in maize genome. Blot-hybridization of one polymorphic RAPD-amplicon demonstrated the presence of its sequence in genomes of all objects under study, so the revealed changes are most likely related to considerable differences in the amounts of PCR products. The obtained results suggest the low level of genome variability in maize tissue culture.